Isolated Peripheral Tuberculous Lymphadenitis: Insights into Diagnostic Delays and Clinical Challenges - Gürcüoğlu, Emel (The European Research Journal, 2026)
Objectives: Peripheral tuberculous lymphadenitis (TB-LAP) is the most common form of extrapulmonary tuberculosis (EPTB) and remains diagnostically challenging due to its low bacillary burden. This study aimed to evaluate diagnostic pathways, microbiological confirmation rates, and treatment outcomes in adult TB-LAP cases. Methods: We retrospectively analyzed 30 adult patients diagnosed with TB- LAP at a tertiary care center between 2021 and 2025. Inclusion criteria were isolated peripheral lymphadenopathy with compatible histopathology, supported by culture, PCR, or clinical-radiological findings. Data regarding diagnostic delay, referral pathways, microbiological yield, and treatment outcomes were collected. Results: Among 158 peripheral lymphadenopathy cases, 52 were diagnosed as TB-LAP, and 30 with complete follow-up data were included in the final analysis. The mean age was 39.2 years, and 83.3% were female. Culture positivity was 28.6%, Polymerase Chain Reaction (PCR) 42.9%, and acid-fast bacilli were detected in only one patient. Overall microbiological confirmation rate was 23.3%. Treatment was successfully completed in most cases, with treatment-related complication rate of 6.7%. Diagnostic delay ≥2 months was observed in 56.7% of patients. Early referral to the infectious diseases clinic significantly reduced diagnostic delay (